Marketing Mix Strategy Implementation for Business Plan at LH Hotel - Jodi Widardi; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2019)
Business in the field of hospitality services is indeed the main attraction for investors and entrepreneurs in starting a business. Hospitality is a business company that provides room accommodation for a place to rest. Usually the hospitality services those who come to go on vacation, meetings, or work. Hotel is one of the supporting factors of tourism to increasing a number of hotel populations’ makes hoteliers have to compete to make more value offered to customers from other hotels. It’s not only buildings and services offered also marketing factors also affect the success of the hotel business, including promotion, communication to the community through events and campaigns using digital marketing. Various existing hotels each has advantages, from building infrastructure, hotel functions, hotel location, services, to the theme they have. All of these factors are strengths and uniqueness that distinguishes them from others. However, how to convey this uniqueness to the community is not an easy mission. There is a need for market research to determine existing needs and strategies for market penetration.